Model Konstruktivistik Terhadap Peningkatan Kemampuan Menulis Teks Ceramah Siswa - Ningrum Ningrum; Muliadi Muliadi; Sitti Rabiah (Universitas Negeri Makassar, 2022)
Abstract. This research aims to describe the influence of constructivistic models on improving the ability to write lecture texts for students in class XI of IPS Sma Negeri 16 Makassar. This research is a class action study. The subject in this study was the students of class XI ips sma Negeri 16 Makassar which amounted to 36 students. This research data was collected from tests of the ability to write lecture and observation texts. Furthermore the data is analyzed using quantitative description analysis and qualitative analysis. The results showed that the activities shown by students from activities that had been carried out in cycles 1 to 2 showed different attitudes. After the action is carried out in cycle 2 students become more active in learning, students are not silent and passive in cycle 1 but students follow the instructions given by researchers, besides that students also show interest and enthusiasm in the learning process. The spirit of students in the learning process is very visible and students more often ask related questions that are not yet understood. Student test scores at the time of student presiklus activities that reached KKM as many as 2 people or by 5%. In cycle 1 activities, students who reached KKM as many as 10 students or by 27% in cycle 2 students who reached KKM as many as 32 students or as many as 88%.Keyword: Reading, Talk Text, Constructivistic model